Family, Community, and Health System Considerations for Reducing the Burden of Pediatric Sickle Cell Disease in Uganda Through Newborn Screening - Nancy S. Green MD; Sanyukta Mathur DrPH, MHS; Sarah Kiguli MBChB, MMed, MHPE; Julie Makani MD, PhD, FRCP, FTAAS; Victoria Fashakin BS; Philip LaRussa MD; Magdalena Lyimo MD; Elaine J. Abrams MD; Lukia Mulumba RN, MSN, FNP; Ezekiel Mupere MBChB, MMed, MS, PhD (SAGE Publishing, 2016)
Sickle cell disease (SCD) is associated with high mortality for children under 5 years of age in sub-Saharan Africa. Newborn sickle screening program and enhanced capacity for SCD treatment are under development to reduce disease burden in Uganda and elsewhere in the region. Based on an international stakeholder meeting and a family-directed conference on SCD in Kampala in 2015, and interviews with parents, multinational experts, and other key informants, we describe health care, community, and family perspectives in support of these initiatives. Key stakeholder meetings, discussions, and interviews were held to understand perspectives of public health and multinational leadership, patients and families, as well as national progress, resource needs, medical and social barriers to program success, and resources leveraged from HIV/AIDS. Partnering with program leadership, professionals, patients and families, multinational stakeholders, and leveraging resources from existing programs are needed for building successful programs in Uganda and elsewhere in sub-Saharan Africa.